Policy roundtable on challenges and opportunities of agri-food trade: The case of Myanmar (ATMI-ASEAN) - Southeast Asian Regional Center for Graduate Study and Research in Agriculture; International Food Policy Research Institute (Southeast Asian Regional Center for Graduate Study and Research in Agriculture, 2019)
The Southeast Asian Regional Center for Graduate Study and Research in Agriculture (SEARCA) and the International Food Policy Research Institute (IFPRI), in partnership with the Ministry of Agriculture, Livestock and Irrigation-Department of Planning (MOALI-DOP) of Myanmar, organized the policy roundtable (PRT) titled “Challenges and Opportunities of Agri-food Trade: The Case of Myanmar.” Under the project Agricultural Transformation and Market Integration in the ASEAN Region: Responding to Food Security and Inclusiveness Concerns (ATMI-ASEAN), the policy roundtable was held on 20 April 2018 in Nay Pyi Taw, Myanmar.